Psychometric properties of the quality of life in short statured youth (QoLISSY) questionnaire within the course of growth hormone treatment - Bloemeke, Janika; Silva, Neuza; Bullinger, Monika; Witt, Stefanie; Dörr, Helmuth-Günther; Quitmann, Julia (Health and Quality of Life Outcomes, 2019)
BackgroundThe Quality of Life of Short Stature Youth (QoLISSY) questionnaire is a patient- and parent-reported outcome measure assessing health-related quality of life (HRQOL) in short stature youth. This study evaluates the psychometric properties of the QoLISSY questionnaire within a German prospective trial of short statured children treated with human growth hormone (hGH).MethodThe instrument was administered to children with idiopathic growth hormone Deficiency (IGHD) and small for gestational age (SGA) before and after 12month of hGH treatment. Children with idiopathic short stature (ISS) served as a reference group receiving no treatment. Psychometric testing included scale distribution characteristics, reliability (internal consistency), criterion-and convergent validity (correlations with the generic KIDSCREEN-Index, inter-correlations among QOLISSY subscales), known-group validity (treatment status, height SDS), and responsiveness analysis (ability to detect change).ResultsOne hundred fifty-two parents and 66 children/adolescents completed both HRQOL assessments. The QoLISSY demonstrated good reliability with Cronbach's alpha > .70. Moderate significant correlations between QoLISSY domains and the KIDSCREEN-10 Index supported criterion validity. Statistically significant differences in HRQOL were observed between treatment groups at baseline with children who were about to start treatment reporting a significantly lower HRQOL compared to the children who will not receive treatment. No significant differences were found between the level of short stature based on height SDS scores ( -2 SDS, > -2 SDS). Furthermore, the instrument detected significant changes in HRQOL between the treated and the untreated group in patient-reports.ConclusionsIn conclusion, the scales showed satisfactory reliability, adequate validity and ability to detect change in self-reported HRQOL within GH treatment. Findings support QoLISSY's further use in clinical trials, offering the opportunity to adequately assess HRQOL from the patients' and caregivers' perspective to improve patient-centered care.
CRIS-Team WoS Importer:2019-04-04